A quarter of patients with type 1 diabetes have co‐existing non‐islet autoimmunity: the findings of a UK population‐based family study. (24th March 2018) - Kozhakhmetova, A.; Wyatt, R. C.; Caygill, C.; Williams, C.; Long, A. E.; Chandler, K.; Aitken, R. J.; Wenzlau, J. M.; Davidson, H. W.; Gillespie, K. M.; Williams, A. J. K.
Summary: Individuals with type 1 diabetes (T1D) are at increased risk of coeliac disease (CD), autoimmune thyroiditis and autoimmune gastritis, but the absolute risks are unclear. The aim of this study was to investigate the prevalence of autoantibodies to tissue transglutaminase (TGA), thyroid peroxidase (TPOA) and gastric H + /K + ‐ATPase (ATPA) and their genetic associations in a well‐characterized population‐based cohort of individuals with T1D from the Bart's–Oxford family study for whom islet autoantibody prevalence data were already available. Autoantibodies in sera from 1072 patients (males/females 604/468; median age 11·8 years, median T1D duration 2·7 months) were measured by radioimmunoassays; HLA class II risk genotype was analysed in 973 (91%) using polymerase chain reaction with sequence specific primers (PCR‐SSP). The prevalence of TGA (and/or history of CD), TPOA and ATPA in patients was 9·0, 9·6 and 8·2%, respectively; 3·1% had two or more autoantibodies. Females were at higher risk of multiple autoimmunity; TGA/CD were associated with younger age and TPOA with older age. ATPA were uncommon in patients under 5 years, and more common in older patients. Anti‐glutamate decarboxylase autoantibodies were predictive of co‐existing TPOA/ATPA. TGA/CD were associated with human leucocyte antigen (HLA) DR3‐DQ2, with the DR3‐DQ2/DR3‐DQ2 genotype conferring the highest risk, followed by DR4‐DQ8/DR4‐DQ8. ATPA were associated with DR3‐DQ2, DRB1*0404 (in males) and the DR3‐DQ2/DR4‐DQ8 genotype. TPOA were associated with the DR3‐DQ2/DR3‐DQ2 genotype. Almost one‐quarter of patients diagnosed with T1D aged under 21 years have at least one other organ‐specific autoantibody. HLA class II genetic profiling may be useful in identifying those at risk of multiple autoimmunity. Abstract : Figure 1. The prevalence of non‐islet autoantibodies in children and young adults with T1D stratified by age group. The prevalence of TGA/CD reduced with age (p<0.0001), while ATPA were uncommon in children under 5 (p<0.05), and the prevalence of TPOA increased with age (p<0.0001).